The Effect of Liquidity on Profitability: An Analytical Study on a sample of Commercial Banks Listed on the Iraq Stock Exchange for the Period 2016-2023 - Rondk Shahin Saifadin (مجلة الغري للعلوم الاقتصادية والادارية)
This study examines the effect of banking liquidity on profitability in five commercial banks listed on the Iraq Stock Exchange over the period 2016–2023. Profitability is measured using Return on Assets (ROA) and Return on Equity (ROE), while liquidity indicators include the Current Ratio (CR), Loan-to-Deposit Ratio (LDR), Deposit-to-Asset Ratio (DTA), and Cash Balance (CASH_BAL). The study employs a descriptive-analytical approach and utilizes panel data analysis through (EViews 10) software. Various statistical techniques are applied, including descriptive statistics, correlation analysis, and the Generalized Least Squares (GLS) model with Cross-Section SUR weights. The findings reveal that CR has a negative impact on both ROA and ROE, LDR positively affects profitability, while DTA and CASH_BAL exhibit a negative influence. Based on these findings, the study recommends enhancing liquidity management to balance financial stability and profitability, optimizing loan portfolios while mitigating credit risk, and ensuring efficient utilization of deposits in productive investments. The study highlights the critical role of effective liquidity management in enhancing the profitability of commercial banks, underscoring the need for well-structured financial strategies to achieve sustainable growth.